The post-entry size adjustment of new small firms - Francesca Lotti; Enrico Santarelli; Marco Vivarelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
The hypothesis underlined in this paper is that apart from infant mortality there is another relevant phenomenon taking place within new-born Small Business Enterprises (SBEs) in the period immediately after entry; namely that the smaller ones among them, having entered with a marked sub-optimal scale,adjust their size towards the mean size exhibited by larger SBEs. In the paper this hypothesis is tested using a cohort of 1,570 new firms, and applying a Gibrat-like specification with sample selection. The hypothesis of a size adjustment by smaller new entrants immediately after entry is confirmed in most selected industries in Italian manufacturing; more specifically, surviving smaller new SBEs show higher rates of growth in the first year (in one case in the first two) immediately after start-up, while they converge towards the average rate of growth of the whole cohort of new SBEs in the following years.
Keywords: 330; Unternehmensgründung; KMU; Betriebsgröße; Schätzung; Italien